2019
DOI: 10.3390/app9214563
|View full text |Cite
|
Sign up to set email alerts
|

Effective Adsorption of Methylene Blue dye onto Magnetic Nanocomposites. Modeling and Reuse Studies

Abstract: In the present study, new adsorbent beads of alginate (A)/maghemite nanoparticles (γ-Fe2O3)/functionalized multiwalled carbon nanotubes (f-CNT) were prepared and characterized by several techniques, e.g., N2 adsorption-desorption isotherms, Fourier transformed infrared spectroscopy (FTIR), X-ray diffraction (XRD), thermogravimetric analysis (TGA/DTG), scanning electron microscopy (SEM), and vibrating sample magnetometry (VSM) and further tested for the adsorption of the dye methylene blue (MB) from water. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 61 publications
1
20
0
Order By: Relevance
“…2E) demonstrated that the variation of peaks intensity and appearance of new peaks which strongly suggested that the removal mechanism of MB dye onto UiO-66/ MIL-101(Fe)-GOCOOH composite involves electrostatic interactions between the MB dye and adsorbent functional groups which is a good agreement with pH results. 63 Moreover, Zr-O and Fe-O centers represent good possibilities for n-p conjugation. This conjugation is conrmed by variation in intensity and the shi of the peaks in the range 440-530 cm À1 .…”
Section: Mechanism Of Mb Dye Adsorptionmentioning
confidence: 99%
“…2E) demonstrated that the variation of peaks intensity and appearance of new peaks which strongly suggested that the removal mechanism of MB dye onto UiO-66/ MIL-101(Fe)-GOCOOH composite involves electrostatic interactions between the MB dye and adsorbent functional groups which is a good agreement with pH results. 63 Moreover, Zr-O and Fe-O centers represent good possibilities for n-p conjugation. This conjugation is conrmed by variation in intensity and the shi of the peaks in the range 440-530 cm À1 .…”
Section: Mechanism Of Mb Dye Adsorptionmentioning
confidence: 99%
“…The hybrid CNTs’ adsorbent reaction behavior could be examined through kinetic behavior. For this experimental data, three kinetic models were used, including pseudo-first-order, pseudo-second-order, and the intraparticle diffusion model [ 57 , 58 ]. To conduct the kinetic study, the Al 3+ that was included varied in concentrations from 3, 5, and 10 mg/L, while the absorption dosage value was fixed at a 13.5 mg and pH of 7 at various time intervals awaiting for the equilibrium state to be attained.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, in the case of the iron supported catalysts, peaks at 18.1 (111), 33.9 (310), 35.6 (311), 43.1 (400), 48.5(420), 62.6 (440), and 64.5 (530), which were attributed to maghemite (-Fe2O3), were identified [35]. It should be noted that these peaks are overlapped with the ones of Ca(OH)2 or CaCO3.…”
Section: Structural Characterization: Xrd and Ftir Analysesmentioning
confidence: 99%